Using Colored Petri Nets for Simulation of Control Systems - Bartkevičius, S.; Mačerauskas, V.; Šarkauskas, K. (Elektronika ir Elektrotechnika, 2003)
Modern control systems are hybrid – continuous or mixed objects are controlled by discrete controllers. Colored Petri nets are theexcellent mean of simulation of control algorithms. Continuous objects can be described by differential equations. These equations canbe represented as a structural scheme. An interface between those to parts of a model is very important as well as evaluation of the time,because it can be one of the factors of control. The simulation system realized in the program package CENTAURUS-C is presented.Interface between both parts of a model is realized via specialized transition, in Petri net, named – process. Three default real variables– $Out, $In and $Prev are used in the interface. A process can carry the value of $Out into a structure of an object as a step signal andreceive signal from any output of blocks in structure as a value of the variable $In. Value of variable $Prev is a value of $Inremembered on previous step of simulation. Variable $Out can be used in an expression of input chord of a process and init the process.Variables $In and $Prev can be used in guard expression of a process to set the end of a process – firing of the specialized transition.Time in the presented system is an attribute of processes and transitions – delay. The delays of transitions are represented by specialexpressions and can be changed dynamically. Ill. 7, bibl. 11 (in Lithuanian; summaries in Lithuanian, English, Russian).Modern control systems are hybrid – continuous or mixed objects are controlled by discrete controllers. Colored Petri nets are theexcellent mean of simulation of control algorithms. Continuous objects can be described by differential equations. These equations canbe represented as a structural scheme. An interface between those to parts of a model is very important as well as evaluation of the time,because it can be one of the factors of control. The simulation system realized in the program package CENTAURUS-C is presented.Interface between both parts of a model is realized via specialized transition, in Petri net, named – process. Three default real variables– $Out, $In and $Prev are used in the interface. A process can carry the value of $Out into a structure of an object as a step signal andreceive signal from any output of blocks in structure as a value of the variable $In. Value of variable $Prev is a value of $Inremembered on previous step of simulation. Variable $Out can be used in an expression of input chord of a process and init the process.Variables $In and $Prev can be used in guard expression of a process to set the end of a process – firing of the specialized transition.Time in the presented system is an attribute of processes and transitions – delay. The delays of transitions are represented by specialexpressions and can be changed dynamically. Ill. 7, bibl. 11 (in Lithuanian; summaries in Lithuanian, English, Russian).